2007
DOI: 10.1007/s10750-007-0592-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of cladocerans reflecting the trophic status of two large and shallow Estonian lakes

Abstract: The role of pelagic cladoceran communities is discussed on the basis of a comparative study conducted in two Estonian lakes, the moderately eutrophic Lake Peipsi (N tot 700, P tot 40 lg l -1 as average of ice-free period of [1997][1998][1999][2000][2001][2002][2003] and in a strongly eutrophic Lake Võ rtsjä rv (N tot 1600, P tot 54 lg l -1 ). The cladoceran community was found to reflect the differences in the trophic state of these lakes. In L. Peipsi, characteristic species of oligo-mesotrophic and eutrophic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
1
18
0
2
Order By: Relevance
“…Long-term investigations of the moderately eutrophic and large Lake Peipsi and the very eutrophic Lake Võrtsjärv have shown that both abundance and biomass of zooplankton increase with eutrophication (Haberman, 1996(Haberman, , 1998. Moreover, the number, biomass and proportion by number and biomass of rotifers increased with tropic state, the proportion of Daphnia of total crustacean biomass decreased, while, in contrast to Danish lakes, copepod biomass decreased (Haberman et al, 2007). In the Estonian lakes, the proportion of rotifers by number and biomass and the biomass of zooplankton are most closely linked with trophic state, while others-as in the Danish lakes-are better indicators of top-down regulating factors.…”
Section: Assessment: Contemporary Samplesmentioning
confidence: 86%
“…Long-term investigations of the moderately eutrophic and large Lake Peipsi and the very eutrophic Lake Võrtsjärv have shown that both abundance and biomass of zooplankton increase with eutrophication (Haberman, 1996(Haberman, , 1998. Moreover, the number, biomass and proportion by number and biomass of rotifers increased with tropic state, the proportion of Daphnia of total crustacean biomass decreased, while, in contrast to Danish lakes, copepod biomass decreased (Haberman et al, 2007). In the Estonian lakes, the proportion of rotifers by number and biomass and the biomass of zooplankton are most closely linked with trophic state, while others-as in the Danish lakes-are better indicators of top-down regulating factors.…”
Section: Assessment: Contemporary Samplesmentioning
confidence: 86%
“…Discrepancies between the trophic status and food resources of these lakes (Kangur et al, 2003) were probably the main cause of such variations. According to Haberman et al (2007), in the course of eutrophication the food supplies of juvenile fish decrease. In strongly eutrophic Lake Võrtsjärv, food conditions are not good for pikeperch fry due to low density of large zooplankters like Eudiaptomus gracilis (Sars), Bosmina berolinensis Imhof, Daphnia spp., and L. kindti .…”
Section: Discussionmentioning
confidence: 99%
“…A decrease occurred in total ciliate abundances in response to the removal of crustaceans, the opposite of what has been most commonly reported previously in similar experiments (Adrian & Schneider-Olt, 1999;Ventelä et al, 2002). The crustacean community of Võ rtsjärv is mostly composed of small cyclopoids (mainly Mesocyclops leuckarti and Thermocyclops oithonides Sars) and small-bodied cladocerans such as Chydorus sphaericus, Daphnia cucullata and Bosmina longirostris; their numbers and biomasses are relatively low, being obviously affected by strong fish predation pressure (Haberman, 1998;Haberman, Laugaste & Nõ ges, 2007) and by unfavourable feeding conditions due to high abundances of filamentous algae and frequent sediment resuspension (Chow-Fraser & Sprules, 1986;Levine, Zehrer & Burns, 2005). The crustacean community of Võ rtsjärv is mostly composed of small cyclopoids (mainly Mesocyclops leuckarti and Thermocyclops oithonides Sars) and small-bodied cladocerans such as Chydorus sphaericus, Daphnia cucullata and Bosmina longirostris; their numbers and biomasses are relatively low, being obviously affected by strong fish predation pressure (Haberman, 1998;Haberman, Laugaste & Nõ ges, 2007) and by unfavourable feeding conditions due to high abundances of filamentous algae and frequent sediment resuspension (Chow-Fraser & Sprules, 1986;Levine, Zehrer & Burns, 2005).…”
Section: Discussionmentioning
confidence: 76%